1994
DOI: 10.1111/j.1471-0528.1994.tb13146.x
|View full text |Cite
|
Sign up to set email alerts
|

The cell adhesion molecule, VCAM‐1, is selectively elevated in serum in pre‐eclampsia: does this indicate the mechanism of leucocyte activation?

Abstract: Objective To determine whether circulating levels of cell adhesion molecules, markers of endothelial damage and leucocyte activation, were increased in pre‐eclampsia. Design Serum was prepared from peripheral venous blood and stored at –70°C. The cell adhesion molecules, VCAM‐1, E‐Selectin and ICAM‐1, were measured by ELISA. Setting Department of Obstetrics and Gynaecology, Royal Infirmary, Glasgow. Subjects Sixteen primigravid women with pre‐eclampsia were recruited for the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
48
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 13 publications
12
48
1
2
Order By: Relevance
“…The significant selective elevation of sVCAM-1 in the serum of preeclamptic women observed in this study confirms the results of some recent reports [5][6][7][8] and is analogous to the previously reported increase of the vasoconstrictors endothelin-1 and von Willebrand factor in the blood of preeclamptic women 9 and to the decrease in the production of the vasodilator prostacyclin in endothelial cells. 10 Several pathways could be involved in the significant elevation of sVCAM-1 in preeclamptic women.…”
Section: Discussionsupporting
confidence: 81%
“…The significant selective elevation of sVCAM-1 in the serum of preeclamptic women observed in this study confirms the results of some recent reports [5][6][7][8] and is analogous to the previously reported increase of the vasoconstrictors endothelin-1 and von Willebrand factor in the blood of preeclamptic women 9 and to the decrease in the production of the vasodilator prostacyclin in endothelial cells. 10 Several pathways could be involved in the significant elevation of sVCAM-1 in preeclamptic women.…”
Section: Discussionsupporting
confidence: 81%
“…This finding not only emphasises that PE is not merely a variant of essential hypertension but supports the concept that endothelial cells are a target in the disorder. Several markers of endothelial Increased endothelin 222 Increased prevalence of antiendothelial antibodies 80 Increased thrombomodulin 223 Increased thromboxane 224 Increased cellular fibronection (cFN) concentration a 225 Increased plasminogen activation activity (PAI-1) 226 Increased soluble VCAM 227 Increased tissue plasminogen activator 228 Increased ICAM a 229…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Some studies reported an increase of sPselectin, sE-selectin, and sICAM-1 [18][19][20]. While others reported no changes [21,22]. In contrast, all studies have reported an increase in sVCAM-1 [21][22][23][24].…”
Section: Discussionmentioning
confidence: 86%
“…Lyall et al [21] reported that serum levels of VCAM-1 and E-selectin were not significantly different between normal and preeclamptic pregnancies. Chaiworapongsa et al [26] suggested that serum levels of ICAM-1 have no differences between normal and preeclamptic pregnancies.…”
Section: Discussionmentioning
confidence: 99%